Steroidal Ammonium Compounds as New Neuromuscular Blocking Agents. (26th January 2016) - Rao, Zhigang; Hu, Hao; Tang, Jiazhi; Liu, Zhiying; Yang, Yue; Qiu, Guofu; Xiao, Yuling; Liu, Peng; Hu, Xianming; Zhou, Xiaoju; Hong, Xuechuan
Abstract : Neuromuscular blocking agents are widely used as an anesthesia auxiliary in surgery, which induce relaxation of skeletal muscles by blocking signal transmission at the neuromuscular junction. Many neuromuscular blocking agents s were developed over the past decades, but none of them fully meets the needs of the clinic by various reasons. In this study, a series of quaternary ammonium steroidal neuromuscular blocking agents were synthesized and evaluated on isolated mouse phrenic nerve–hemidiaphragms for their bioactivities. The initial separation of mono‐ and bis‐quaternary ammonium compounds turned out to be very challenging on regular silica gel chromatography. Therefore, a facile purification method, in which the silica gel was pretreated with methanolic sodium bromide solution, was finally achieved. Compounds3g (0.36 μ m ) and4g (0.37 μ m ) exhibited excellent neuromuscular blocking activities, which were about sixfold to sevenfold higher in potency than that of rocuronium (2.50 μ m ). In addition, other bis‐quaternized compounds also showed good potencies close to that of rocuronium. Furthermore, the preliminary structure–activity relationship of this series was also elucidated. Benzyl group was found to be a promising quaternary group in this series. Abstract : Two compounds exhibited excellent in vitro neuromuscular blocking activities. In vitro IC50:3g (0.36 μ m ) and4g (0.37 μ m ). A continuous structure–activity relationship (SAR) of 3, 16‐mono/bis‐ammonium steroidal compounds as neuromuscular blocking agents were elucidated based on previous work. Facile thin‐layer chromatography (TLC) and column chromatography (CC) method were established for purification of steroidal ammonium compounds.